2011
DOI: 10.1242/dev.056564
|View full text |Cite
|
Sign up to set email alerts
|

p120 catenin is required for normal renal tubulogenesis and glomerulogenesis

Abstract: Defects in the development or maintenance of tubule diameter correlate with polycystic kidney disease. Here, we report that absence of the cadherin regulator p120 catenin (p120ctn) from the renal mesenchyme prior to tubule formation leads to decreased cadherin levels with abnormal morphologies of early tubule structures and developing glomeruli. In addition, mutant mice develop cystic kidney disease, with markedly increased tubule diameter and cellular proliferation, and detached luminal cells only in proximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 60 publications
1
54
0
Order By: Relevance
“…In fact, on average, p120-ablated tissues tend to retain 25-50% of cadherin levels found in control tissue Perez-Moreno et al, 2006;Smalley-Freed et al, 2010). In vivo correlations, where available, appear to support the in vitro data in that p120 family members have been found in tissues in which p120 ablation does not result in complete cadherin loss (Marciano et al, 2011;Perez-Moreno et al, 2006). However, whether endogenous p120 family members compensate for p120 loss in vivo has yet to be directly demonstrated in any tissue (e.g.…”
Section: Research Article P120-catenin In Mammary Developmentmentioning
confidence: 80%
See 3 more Smart Citations
“…In fact, on average, p120-ablated tissues tend to retain 25-50% of cadherin levels found in control tissue Perez-Moreno et al, 2006;Smalley-Freed et al, 2010). In vivo correlations, where available, appear to support the in vitro data in that p120 family members have been found in tissues in which p120 ablation does not result in complete cadherin loss (Marciano et al, 2011;Perez-Moreno et al, 2006). However, whether endogenous p120 family members compensate for p120 loss in vivo has yet to be directly demonstrated in any tissue (e.g.…”
Section: Research Article P120-catenin In Mammary Developmentmentioning
confidence: 80%
“…Arvcf, p0071 (plakophilin 4) and d-catenin using wellcharacterized antibodies (Hofmann et al, 2009;Marciano et al, 2011;Walter et al, 2008;Walter et al, 2010). Family members demonstrated membranous and cytoplasmic localization in the mammary epithelium, which was not altered in the absence of p120 (Fig.…”
Section: Development 1758mentioning
confidence: 99%
See 2 more Smart Citations
“…Because membrane polarity proteins, e.g. E-cadherin, are known to be destabilized in the kidneys of PKD and NPHP patients (Charron et al, 2000;Marciano et al, 2011;Okada et al, 2000;Rocco et al, 1992;Wilson, 2011), and because we also observed a similar phenotype in pcy mice (supplementary material Fig. S4B), it is probable that both impairment of Slp2-a-mediated Rap-ezrin signaling and enhancement of cAMP-induced RapGEF signaling ultimately activate Rac1 and that the activated Rac1 causes cell spreading by destabilizing E-cadherin at the cell-cell junctions in the kidneys of pcy mice (supplementary material Fig.…”
Section: Discussionmentioning
confidence: 99%